Sayyid Muhammad ‘Alawi al-Maliki’s View on Orientalist Criticism of Imam Malik’s Book al-Muwattha’ - Fadhil Ramadhani; Muhid (al-Afkar, Journal For Islamic Studies, 2025)
This study examines Sayyid Muhammad ‘Alawi al-Maliki’s defense against Orientalist critiques of al-Muwattha’, authored by Imam Malik. These critiques primarily focus on the use of mursal (disconnected) hadiths, insufficient attention to the chain of transmission (sanad), and the perception that the book is more a work of jurisprudence than hadith. In his book “Imam Darul Hijrah: Malik Ibn Anas Radiyallahu ‘anhu”, Sayyid Muhammad argues that Imam Malik’s methodology was grounded in rigorous scholarly principles, characterized by high selectivity in assessing both the chain of transmission and the content of hadiths. He asserts that al-Muwattha’ not only reflects the excellence of Madinan traditions but also retains historical and methodological significance in the study of hadith and Islamic jurisprudence. This study employs a descriptive-analytical approach to explore Sayyid Muhammad’s arguments in response to Orientalist critiques, including the views of Carl Brockelmann and Fuat Sezgin, who regarded the book as lacking authority as a hadith reference. The findings reveal that al-Muwattha’ holds a pivotal position in the Islamic intellectual tradition, with its unique methodology integrating hadith and jurisprudence. By refuting Orientalist claims, this study reaffirms the validity of al-Muwattha’ as a primary reference in the study of hadith and Islamic law.